Association of diet practice and glycaemic control among type 2 diabetes mellitus patients attending primary care clinic in Kuala Lumpur. - , Hasimah Ismail; , Tahir Aris; , Rashidah Ambak; Lim, Kuang Kuay (Universiti Kebangsaan Malaysia, 2014)
Healthy dietary practice is important in preventing diabetes, managing existing diabetes, and preventing, or at least slowing the rate of diabetes complication development. It is, therefore, important at all levels of diabetes prevention. The objective of this study was to determine the association of dietary practice with glycaemic control among Type 2 diabetes mellitus(T2DM) patients, who received treatment from an urban Health Clinic in Kuala Lumpur.A total of 307 patients with T2DM aged 18 years and above participated in this study. A pre-tested structured questionnaire with guided interview was used to collect information on socio-demographic, clinical and dietary practice. Anthropometric and biological measurements were also taken. Descriptive statistics and Chi-square were used in the data analysis. Good glycaemic control was defined as HbA1c level less than 6.5%.The prevalence of good glycaemic control was only 27% (n=83). The highest percentage of good glycaemic control were among male patients (29.1%),aged 60 and above (33.3%), educational level of primary school (35.4%) and those with monthly income group between RM1001 to RM1500 (32.0%). About three quarter of T2DM patient (n=224) had poor control of HbA1c (≥6.5%). Age (p=0.045) and working status (p=0.039) had significant relationship with the level of HbA1c. Dietary practice showed no significant relationship with the HbA1c level.Effective interventional health education strategies are needed, focussing on modification of dietary behaviour in order to achieve glycaemic control among diabetic patients.